The Impact of Physical Distancing in the Pandemic Situation: Considering the Role of Loneliness and Social Brain - Morese, Rosalba; Longobardi, Claudio (Frontiers in Psychology, 2022)
The new normal has made social distancing a new way of experiencing sociality. Social neuroscience has for a long time been concerned with studying the beneficial effects of social relationships, of physical contact. It is known that physical contact activates neurophysiological processes that reduce the perception of discomfort and even physical pain. So in the absence of physical contact, our social brain may be modulated differently when we are with others. But what could be the long-term effects of this normality? This mini-review focuses on highlighting with the support of social neuroscience evidence such as isolation, distancing can affect people's health.